One- and two-dimensional penta-graphene-like structures - Laranjeira, José A.S. [UNESP]; Martins, Nicolas F. [UNESP]; Azevedo, Sergio A. [UNESP]; Fabris, Guilherme S.L.; Sambrano, Julio R. [UNESP] (Elsevier, 2023)
The discovery of graphene led to the emergence of a two-dimensional (2D) world and the investigation of numerous 2D carbon allotropes through computational simulation methods. Among these, penta-graphene (PG) has received significant attention and has served as the basis for several new 2D inorganic structures. In this context, this study aimed to investigate one- and two-dimensional PG-like structures (P-XC2 where X = C, Si or Ge) and their electronic, structural, dielectric, piezoelectric and catalytic properties via density functional theory simulations. The results showed that P-XC2 systems have an indirect band gap energy ranging from 2.65 to 3.55 eV. Furthermore, P-GeC2 exhibits the highest dielectric and piezoelectric constants values, followed by P-SiC2 and P-GeC2, while penta-graphene has higher elastic constants compared to P-SiC2 and P-GeC2. Notably, armchair and zigzag nanotubes exhibit elastic constants closer to those observed for the respective 2D structure, with penta-graphene showing the biggest differences. Additionally, smaller nanotubes exhibit the largest dielectric constant, which is larger than the respective monolayers. Finally, the band alignment indicates that P-XC2 and their respective nanotubes could favor hydrogen production through water splitting.
Keywords: DFT; Monolayer; Nanotubes; Penta-GeC2; Penta-graphene; Penta-SiC2